Pengaruh Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) Terhadap Efektivitas, Kinerja Pengguna Dan Dampak Pada Kualitas Laporan Keuangan Balai Guru Penggerak Indonesia Timur (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to determine the effect of the implementation of institution-level financial application systems on effectiveness, user performance and impact on the quality of financial statements. This type of research uses causal explanatory research methods with a quantitative approach. The data collection technique in this study was carried out by distributing questionnaires in the form of google forms with a 5-point likert scale. The analysis tool used in this study used SmartPLS. The results of this study show that: 1). The implementation of SAKTI affects user effectiveness; 2). The implementation of SAKTI affects user performance; 3). The implementation of SAKTI does not affect the quality of financial statements; 4). User effectiveness affects the quality of financial statements; 5). User performance has no effect on the quality of financial statements.